2018
DOI: 10.1111/jgh.14083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of clinically evident portal hypertension on clinical outcome of patients with hepatocellular carcinoma treated by transarterial chemoembolization

Abstract: The presence of CEPH should be considered as a major negative prognostic factor for patients with HCC who will undergo TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 30 publications
4
29
3
Order By: Relevance
“…Despite current advances in the diagnosis of HCC, the majority of patients are not eligible for surgical treatment due to late diagnosis. Moreover, the five-year survival rate of patients undergoing surgical resection is disappointingly low [ 3 ]. Tumor proliferation and apoptosis plays an important role in the occurrence and development of HCC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite current advances in the diagnosis of HCC, the majority of patients are not eligible for surgical treatment due to late diagnosis. Moreover, the five-year survival rate of patients undergoing surgical resection is disappointingly low [ 3 ]. Tumor proliferation and apoptosis plays an important role in the occurrence and development of HCC [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the presence of CSPH precludes patients from undergoing surgical resection for HCC [19], but less attention has been paid to other loco-regional therapies. However, two studies have recently reported that CSPH is a major negative prognostic factor in patients treated with DEB-TACE [10,20].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the heterogeneity of TACE candidates, patient selection must be carefully carried out. Underlying chronic liver disease is exacerbated by this procedure, especially in patients with diminished liver reserve [10]. Several algorithms have been recently reported to predict HCC prognosis in an attempt to optimize chemoembolization treatments, but few data have been obtained from DEB-TACE procedures [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…For HCC patients with cirrhosis who underwent TACE, Nam Hee Kim et al found that PH was a major negative factor [24]. However, Xiao et al found that hepatectomy provided better long-term prognosis for HCC patients with PH than TACE and ablation [25].…”
Section: Discussionmentioning
confidence: 99%